Postmodification of voxelotor (GBT 440) via [Rh]-catalyzed cross dehydrogenative coupling with olefins br - Kalshetti, Rupali G.; Rajput, Raveena; Motiwala, Zenia; Reddy, D. Srinivasa; Kulkarni, Kiran A.; V. Ramana, Chepuri (Bioorganic & Medicinal Chemistry Letters, 2022)
The directed Rh(III)-catalyzed cross dehydrogenative coupling of the pyrazole unit of the GBT-440 scaffold has been explored with simple as well as conjugated olefins to synthesize post-functionalized GBT-440 analogues. The screening of these synthesized compounds for improving the oxygen binding efficiency of the hemoglobin isolated from the sickled red blood cells revealed that some of these compounds are as good as GBT-440.
Keywords: CDC Coupling; GBT-440 (Voxelotor); Rh(III) catalysis; sickle cell anemia